Prevalence and Correlates of Food Insecurity Among Children Across the Globe - Audrey L. Pereira; Sudhanshu Handa; Goran Holmqvist (United Nations, 2017)
Target 2.1 of the Sustainable Development Goals calls to end hunger, in all its forms, by 2030. Measuring food security among children under age 15, who represent a quarter of the world’s population, remains a challenge and is unfeasible for global monitoring. The SDG framework has agreed to use the Food Insecurity Experience Scale (FIES) to measure moderate and severe food insecurity. The FIES is an experience-based metric that reports food-related behaviours on the inability to access food due to resource constraints. We present the first global estimates of the share and number of children below age 15, who live with a respondent who is food insecure.